REGIONAL ASSET MANAGEMENT IN SOUTHEAST MINAHASA REGENCY REGENCY FINANCIAL AND REVENUE MANAGEMENT AGENCY: PENGELOLAAN ASET DAERAH DI BADAN PENGELOLAAN KEUANGAN DAN PENDAPATAN DAERAH KABUPATEN MINAHASA TENGGARA - Enrico Ryan Sarilim; Novie Revli Pioh; Shirley YVI Goni (SOSIOEDUKASI, 2023)
This study aims to analyze the management of regional assets in the Regional Revenue and Financial Management Board of Southeast Minahasa Regency. The research method used in this study uses a qualitative approach. The data used consists of primary data and secondary data. The informants in the study were taken using a purposive sampling technique with a total of 5 people. The research focus is based on management principles consisting of planning, implementation or utilization and supervision. The data collection was carried out by means of observations, interviews and documentation which were then analyzed in three stages, namely data reduction, data presentation and conclusion drawing. The results of the study show that the management of regional assets in the BPKPD of Southeast Minahasa Regency is carried out in advance, namely each SKPD within the Government of Southeast Minahasa Regency submits for the use of the assets needed, in this case the use of regional property which must be accompanied by supporting documents as part of the requirements administration which aims to determine the utilization of regional assets